Muscle magnetic resonance imaging in myotonic dystrophy type 1 (DM1): Refining muscle involvement and implications for clinical trials. (6th December 2021) - Garibaldi, Matteo; Nicoletti, Tommaso; Bucci, Elisabetta; Fionda, Laura; Leonardi, Luca; Morino, Stefania; Tufano, Laura; Alfieri, Girolamo; Lauletta, Antonio; Merlonghi, Gioia; Perna, Alessia; Rossi, Salvatore; et al.
Abstract: Background: Only a few studies have reported muscle imaging data on small cohorts of patients with myotonic dystrophy type 1 (DM1). We aimed to investigate the muscle involvement in a large cohort of patients in order to refine the pattern of muscle involvement, to better understand the pathophysiological mechanisms of muscle weakness, and to identify potential imaging biomarkers for disease activity and severity. Methods: One hundred and thirty‐four DM1 patients underwent a cross‐sectional muscle magnetic resonance imaging (MRI) study. Short tau inversion recovery (STIR) and T1 sequences in the lower and upper body were analyzed. Fat replacement, muscle atrophy and STIR positivity were evaluated using three different scales. Correlations between MRI scores, clinical features and genetic background were investigated. Results: The most frequent pattern of muscle involvement in T1 consisted of fat replacement of the tongue, sternocleidomastoideus, paraspinalis, gluteus minimus, distal quadriceps and gastrocnemius medialis. Degree of fat replacement at MRI correlated with clinical severity and disease duration, but not with CTG expansion. Fat replacement was also detected in milder/asymptomatic patients. More than 80% of patients had STIR‐positive signals in muscles. Most DM1 patients also showed a variable degree of muscle atrophy regardless of MRI signs of fat replacement. A subset of patients (20%) showed a 'marbled' muscle appearance. Conclusions: Muscle MRI is a sensitive biomarker of disease severity alsofor the milder spectrum of disease. STIR hyperintensity seems to precede fat replacement in T1. Beyond fat replacement, STIR positivity, muscle atrophy and a 'marbled' appearance suggest further mechanisms of muscle wasting and weakness in DM1, representing additional outcome measures and therapeutic targets for forthcoming clinical trials. Abstract : We refined the pattern of muscle involvement in DM1 by upper and lower body muscle magnetic resonance imaging (MRI), identifying the most frequent pattern of fat replacement and confirming that muscle MRI is a sensitive biomarker of disease burden in DM1. We also observed: STIR‐positive muscles in 80% of patients preceding fat replacement, muscle atrophy in muscles unreplaced by fat, and progeroid muscle appearance supporting a premature muscle senescence. Our findings provide novel insights into the pathophysiological mechanisms of muscle wasting and weakness in DM1, and could represent additional outcome measures and therapeutic targets for forthcoming clinical trials.